Impacts of Entry by Counterfeiters* - Qian, Yi (Quarterly Journal of Economics, 2008)
This paper uses a natural experiment to test the impact of counterfeiting under weak intellectual property rights. I collect new panel data from Chinese shoe companies from 1993–2004. By exploiting the discontinuity of government enforcement efforts for the footwear sector in 1995 and the differences in authentic companies' relationships with the government, I identify and measure the effects of counterfeit entry on authentic prices, qualities, and other market outcomes. The results show that brands with less government protection differentiate their products through innovation, self-enforcement, vertical integration of downstream retailers, and subtle high-price signals. These strategies push up authentic prices and are effective in reducing counterfeit sales.